The role of teacher pedagogical competence and communication culture in the formation of reading literacy - Yuldasheva, Iroda; Kurbanova, Bakhtikhon Kochkorbayevna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
This scientific thesis is devoted to an in-depth analysis of the fundamental importance of the teacher's pedagogical competence and communication culture in the process of forming reading literacy. The study examines the decisive role of the teacher's personality in the development of linguistic, speech, socio-cultural and compensatory competencies of students in the conditions of modern educational paradigms. In particular, the teacher's professional skills, the ability to use innovative pedagogical technologies, and the culture of organizing mutual relations in the educational process in a democratic and respectful spirit are assessed as the main factors that directly affect the quality and effectiveness of reading literacy.